Assessment of Heavy Metal Contents in Blue Swimming Crab from the Northeastern Mediterranean Sea, Mersin Bay, Turkey - Olgunoglu, Mine Perçin; Olgunoglu, Ilkan Ali (Challenging Issues on Environment and Earth Science Vol. 6, 2021)
The concentrations of cadmium (Cd), lead (Pb), copper (Cu), zinc (Zn), chromium (Cr), aluminium (Al), and iron (Fe) in the carapace meat of female and male blue swimming crabs (Portunus segnis) from the northeastern Mediterranean Sea in the Gulf of Mersin, Turkey, are investigated in the current study . The order of average heavy metal concentrations in carapace meat samples in both male and female species was Zn>Fe >Cu>Al>Mn>Cr>Pb. From the obtained results, the levels of some metals such as Cu, Zn, and Fe were higher than the acceptable values for human consumption designated by various health organizations. The comparison of our results with previous studies showed that blue swimming crab (Portunus segnis) have been contaminated with heavy metals. The occurrence of high levels of Cu, Zn, and Fe in the aquatic environment is thought to be a result of industrial and maritime traffic activities in Mersin Bay. It may be suggested that continuous care must be taken – especially according to the season – to biomonitor the heavy metal levels if they always exceed the maximum permitted concentrations for human consumption.